2017
DOI: 10.1038/srep44264
|View full text |Cite
|
Sign up to set email alerts
|

The Contrast Enhancement of Intracranial Arterial Wall on High-resolution MRI and Its Clinical Relevance in Patients with Moyamoya Vasculopathy

Abstract: The purpose of this study is to investigate the characteristics of intracranial vessel wall enhancement and its relationship with ischemic infarction in patients with Moyamoya vasculopathy (MMV). Forty-seven patients with MMV confirmed by angiography were enrolled in this study. The vessel wall enhancement of the distal internal carotid artery, anterior cerebral artery and middle cerebral artery was classified into eccentric and concentric patterns, as well as divided into three grades: grade 0, grade 1 and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Among the 166 steno-occlusive lesions detected by HRVWI, 6.02% of lesions only showed contrast enhancement, which is lower in comparison with the previously published data, which accounted for 70%-93%. 1,3,15,16 This may be related to the characteristics of the population under study or might be related to the small sample size. There is evidence that MMD is primarily a proliferative disease of the intima and smooth muscles that leads to vascular stenosis and that concentric enhancement may represent hyperproliferation of vessel components.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 166 steno-occlusive lesions detected by HRVWI, 6.02% of lesions only showed contrast enhancement, which is lower in comparison with the previously published data, which accounted for 70%-93%. 1,3,15,16 This may be related to the characteristics of the population under study or might be related to the small sample size. There is evidence that MMD is primarily a proliferative disease of the intima and smooth muscles that leads to vascular stenosis and that concentric enhancement may represent hyperproliferation of vessel components.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 1 study, 19.6% of ACAs showed contrast enhancement. 3 We also studied the role of HRVWI to possibly predict a future event based on its characteristic findings. It was observed that grade II enhancing lesions were significantly associated with ischemic events within 4 weeks of imaging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations